Review on Engineering Applications of Designed Polymers to Protect Electrical Equipment - Dr. Nagham Mahmood Aljamali,; Dr. Huda Sabah Hassen, (Journal of Power Electronics and Devices, 2021)
Electroactive polymers are a polymer that demonstrate a change in the size or shape when roused by an electric field. The most common applications for this type of material are actuators and sensors. One of the distinctive engineering properties of electroactive polymers is that no matter how much crushing force they are subjected to, they will maintain large engineering forces and last for long periods of time. The older mechanical actuators are made of piezoelectric ceramic materials. These materials are able to resist large forces and these forces will only deform a small percentage of them. It was demonstrated in the late 1990s that some EAPs can withstand stresses up to (80%), which is far greater than the tolerance of any ceramic-engineered mechanical actuator. One of the most shared applications of electrically active engineering polymers is in the field of robotics and the artificial muscle development and therefore electrically active polymers are frequently referred to as artificial muscle.